2007
DOI: 10.1097/smj.0b013e31802fa327
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Periodontal Treatment on Metabolic Control of Hypercholesterolemia

Abstract: The present study indicates that periodontitis causes changes in total and LDL cholesterol levels and local periodontal treatment resulted in a significant decrease in these markers. These results suggest a potential effect of periodontitis-driven systemic inflammation on lipid metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 39 publications
3
39
1
Order By: Relevance
“…These results do not agree with those of Oz et al (29), who assessed the influence of periodontal therapy on hypercholesterolemia metabolic control in patients with periodontitis and reported a significant reduction in TC and LDL compared with initial values.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…These results do not agree with those of Oz et al (29), who assessed the influence of periodontal therapy on hypercholesterolemia metabolic control in patients with periodontitis and reported a significant reduction in TC and LDL compared with initial values.…”
Section: Discussioncontrasting
confidence: 56%
“…The patients in this study remained obese until the end of the experiment, suggesting that the reduction of these parameters is likely related to periodontal therapy. Considering that periodontitis can also alter lipid profile (11,30,31), its treatment may reduce some markers such as TC and LDL (29). In addition to treating periodontitis, the dentist should advise the patient about additional risk factors that may interfere with the disease or treatment results including diet, body weight, lifestyle, and environmental stress (32), and also emphasize that help from a physician and nutritionist will be very beneficial to the treatment, thus targeting obesity as well as periodontitis simultaneously (33).…”
Section: Discussionmentioning
confidence: 99%
“…Losche et al (2005) did not observe alterations in total cholesterol, LDL, HDL, or TGs following therapy, while Oz (Oz et al 2007) and Duan (Duan et al 2009) found that total cholesterol and LDL levels decreased. Montebugnoli observed decreased circulating oxLDL levels following intensive periodontal therapy (Montebugnoli et al 2005).…”
Section: Dyslipidemia Lipid Peroxidation and Inflammationmentioning
confidence: 99%
“…When one single study (Oz et al 2007) was removed from the data, the heterogeneity reduced (p < 0.65, I squared of 0.00).…”
Section: Periodontal Treatment and Cvd Outcomes S87mentioning
confidence: 99%
“…Two RCTs (D'Aiuto et al 2005(D'Aiuto et al , 2006) examined a sample of otherwise healthy individuals affected by severe generalized periodontitis and showed that non-surgical periodontal treatment caused reductions in total and LDL-C levels at 2 and 6 months follow-up. In another RCT, Oz et al (2007) performed periodontal treatment in 50 individuals also suffering from hypercholesterolemia and evaluated their serum lipid concentrations 3 months after the treatment. There was a substantial decline in TC and LDL-C profiles in the treatment group and between the two groups.…”
Section: Periodontal Treatment and Cvd Outcomes S87mentioning
confidence: 99%